Improving patient care via development of a protein‐based diagnostic test for microbe‐specific detection of chronic rhinosinusitis. (2nd October 2013) - Das, Subinoy; Rosas, Lucia E.; Jurcisek, Joseph A.; Novotny, Laura A.; Green, Kari B.; Bakaletz, Lauren O.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The hypothesis is that signature bacterial proteins can be identified in sinus secretions via high‐throughput, proteomic based techniques. Nontypeable Haemophilus influenzae (NTHI) is the most common bacterial pathogen associated with sinusitis and serves as proof of principle pathogen for identifying biomarkers. Study Design In vitro and in vivo studies using proteomic‐based analysis of cultures of NTHI and a novel, experimental chinchilla polymicrobial sinusitis model. Methods Nano‐liquid chromatography /tandem mass spectrometry (nano‐LC‐MS/MS) was performed to annotate the secretome from an NTHI biofilm. A model of NTHI‐induced sinusitis was developed in a chinchilla, and NTHI proteins were detected in chinchilla secretions. A reference standard RT–PCR‐based assay was adapted to allow for sensitivity and specificity testing of the identified signature biomarkers in human patients. Results Outer membrane proteins P2 (OMP‐P2) and P5 (OMP‐P5) were identified as promising candidates for the detection of NTHI biofilms and positively detected in nasopharyngeal secretions of chinchillas experimentally infected with NTHI. An RT‐PCR based test for the presence of NTHI biofilms demonstrated 100% sensitivity and 100% specificity when tested against eight unique strains commonly found in human bacterial rhinosinusitis. Conclusions Proteomic analysis was successful in identifying signature proteins for possible use as a biomarker for chronic rhinosinusitis (CRS). OMP‐P2 and OMP‐P5 were validated as promising candidates and were positively detected from nasopharyngeal secretions from chinchillas experimentally infected with NTHI. Collectively, these data support the use of OMP‐P2 and OMP‐P5 as biomarkers for a human clinical trial to develop a point‐of‐care medical diagnostic test to assist in the diagnosis and treatment of CRS. Level of Evidence NA. Laryngoscope, 124:608–615, 2014